AF394, AF395, AF397, AK142, AK652, AN193 and AV441 antibodies label the GFP protein by western blot - Guilhen, Cyril; Vigneau, Mathieu; Tamrat, Bethania; Siebenmann, Emma; Khadam-Al-Jame, Tasnim; Gillet, Hugo; Garrido, Eva; Farhat, Hania; Berlincourt, Jade; Baltazar, Luca; Arbez, Tess; Adomako, Benjamin; et al. (Antibody Reports, 2022)
The recombinant antibodies AF394, AF395, AF397, AK142, AK652, AN193 and AV441 detect the GFP protein by western blot.